2023
DOI: 10.3390/en16237768
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Sustainable Development of Solar Photovoltaic Tracking System Technology

Zihan Yang,
Zhiquan Xiao

Abstract: In the face of the traditional fossil fuel energy crisis, solar energy stands out as a green, clean, and renewable energy source. Solar photovoltaic tracking technology is an effective solution to this problem. This article delves into the sustainable development of solar photovoltaic tracking technology, analyzing its current state, limiting factors, and future trends. The adjustment of solar panel orientation using solar tracking technology to maximize energy generation efficiency has been widely implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 146 publications
0
0
0
Order By: Relevance
“…The sustainable development of solar photovoltaic tracking technology is being driven by the integration of smart and digital technologies, aiming for higher precision, broader applications, and lower costs. This includes a focus on photovoltaic materials and manufacturing innovations and energy efficiency improvements [94]. A case study in Incheon, South Korea, demonstrated that a tracking PV system installed in the roof area of a commercial building generated 26.8-35.5% more electricity annually than a fixed system.…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainable development of solar photovoltaic tracking technology is being driven by the integration of smart and digital technologies, aiming for higher precision, broader applications, and lower costs. This includes a focus on photovoltaic materials and manufacturing innovations and energy efficiency improvements [94]. A case study in Incheon, South Korea, demonstrated that a tracking PV system installed in the roof area of a commercial building generated 26.8-35.5% more electricity annually than a fixed system.…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%
“…Improve capacity, cycle life, and safety for excess solar energy [96,97] Solar thermal energy stands out as a versatile and efficient renewable energy source, harnessing the sun's heat to generate electricity, as well as providing heating and cooling solutions. This technology employs solar thermal collectors to absorb sunlight and convert it into heat, which can then be utilized to produce steam for driving turbines and generating electricity or directly applied in heating and cooling systems [90][91][92][93][94][95][96][97][98][99][100][101]. Distinguishing between solar thermal and solar photovoltaic (PV) energy highlights the unique approaches and applications of these technologies in harnessing solar energy.…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%
“…A system that converts solar energy into electrical energy by utilizing the photovoltaic effect of semiconductors is known as a solar power generation system. Solar power generation is a viable option to alleviate the energy crisis, contributing to mitigating climate change, reducing energy costs, and promoting the transition to green energy [1]. Compared with traditional photovoltaic power generation technology, distributed photovoltaic power generation is a novel mode of integrated power generation and energy utilization.…”
Section: Introductionmentioning
confidence: 99%